Skeletal parasympathetic innervation communicates central IL-1 signals regulating bone mass accrual - Bajayo, Alon (National Academy of Sciences, 2012)
Bone mass accrual is a major determinant of skeletal mass, governed by bone remodeling, which consists of bone resorption by osteoclasts and bone formation by osteoblasts. Bone mass accrual is inhibited by sympathetic signaling centrally regulated through activation of receptors for serotonin, leptin, and ACh. However, skeletal activity of the parasympathetic nervous system (PSNS) has not been reported at the bone level. Here we report skeletal immune-positive fibers for the PSNS marker vesicular ACh transporter (VAChT). Pseudorabies virus inoculated into the distal femoral metaphysis is identifiable in the sacral intermediolateral cell column and central autonomic nucleus, demonstrating PSNS femoral innervation originating in the spinal cord. The PSNS neurotransmitter ACh targets nicotinic (nAChRs), but not muscarinic receptors in bone cells, affecting mainly osteoclasts. nAChR agonists up-regulate osteoclast apoptosis and restrain bone resorption. Mice deficient of the α(2)nAChR subunit have increased bone resorption and low bone mass. Silencing of the IL-1 receptor signaling in the central nervous system by brain-specific overexpression of the human IL-1 receptor antagonist (hIL1ra(Ast)(+/+) mice) leads to very low skeletal VAChT expression and ACh levels. These mice also exhibit increased bone resorption and low bone mass. In WT but not in hIL1ra(Ast)(+/+) mice, the cholinergic ACh esterase inhibitor pyridostigmine increases ACh levels and bone mass apparently by inhibiting bone resorption. Taken together, these results identify a previously unexplored key central IL-1–parasympathetic–bone axis that antagonizes the skeletal sympathetic tone, thus potently favoring bone mass accrual.